THE EFFECT OF EMPLOYEE ENGAGEMENT, WORK-LIFE BALANCE, AND WORK STRESS ON THE PRODUCTIVITY OF TOYOTA AUTO 2000 PLJU PALEMBANG EMPLOYEES - Dinda Dwi Deninta; Endah Dewi Purnamasari; Hamid Halin (Universitas KH. Abdul Chalim Mojokerto, 2026)
Employee productivity is an important factor in supporting company performance. This study aimed to analyze the effects of employee engagement, work-life balance, and work stress on employee productivity at Toyota Auto 2000 Plaju Paleimbang. This study employed a quantitative approach using questionnaire-based data collection distributed to employees. Data were analyzed using multiple linear regression with the assistance of SPSS veirsion 29. The results indicated that employee enggement and work-life balance had significant effects on employee productivity, while work stress did not have a significant effect. Simultaneously, employee engagement, work-life balance, and work stress influenced employee productivity. These findings indicate that improving employee engagement and maintaining work-life balance are essential to enhance employee productivity.